Causality, Confounding, and Simpson's Paradox - Asad Zaman; Taseer Salahuddin (International Econometric Review (IER), 2020)
This is an introductory article which explains the importance of explicit consideration and modeling of causality, contrary to current econometric practice, in order to use data set for extraction of meaningful information. One of the easiest to understand approaches to causality is via Simpson's paradox. We will use this paradox, framed in different real-world contexts, to provide an introduction to basic concepts of causality.
Keywords: C0; C1; 330; Simpson's Paradox; Causality; Econometrics; Confounders; Mediators